The German News Coverage of Poland during the Polish EU Presidency Termin2011 - WÖHLERT, ROMY (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2013)
This paper summarizes the key features of the German print media news coverage on Poland throughout the timeframe of the Polish EU Presidency term in 2011. Results stem from a quantitative content analysis of three daily newspapers and one newsmagazine that were analyzed over a timeframe of 7 months from June 2011 to January 2012. Being one of the founding countries of the EU, Germany is one of the “EU-heavyweights”, regarding its population size and its political standing. Furthermore, compared to other EU members, the country has a rather supportive position towards its own EU membership as well as to EU-related matters. This position was slightly shaken more recently by the EU financial crisis, but remains more positive still than in many other EU countries. However, Germany also has a very special and not always conflict-free relationship to its neighboring country Poland. Both aspects are crucial to bear in mind when the German news coverage on Poland during the presidency term is taken into view. The paper shows that the Polish EU presidency did not change the overall thematic focus of the German news coverage on Poland. The frame of perceptions of Poland shifted towards a more EU-related dimension only slightly and temporarily, but overall, deeper-rooted frames of perception as well as characteristic news factors shaped the German news coverage on Poland.